Penta-Octa B4C2N3: A New 2D Material for High-Performance Energy Applications - Chen, Xihao; Wang, Jiazhuo; Martins, Nicolas F. [UNESP]; Sambrano, Julio R. [UNESP]; Laranjeira, José A. S. [UNESP] (American Chemical Society (ACS), 2025)
Penta-octagraphene (POG) is a newly suggested two-dimensional carbon allotrope recognized for its distinct configuration and fascinating electronic characteristics. This work presents a new inorganic counterpart of POG, named POG-B4C2N3, designed through density functional theory (DFT) calculations. This new structure exhibits a direct band gap transition at the X-point, measured at 0.32/0.86 eV with PBE/HSE functionals. Mechanical properties were comprehensively assessed, showcasing its Young’s modulus (Ymax/Ymin = 157.12/100.84 N/m) and shear modulus (Gmax/Gmin = 83.03/38.09 N/m), alongside Poisson’s ratio (νmax/νmin = 0.58/-0.09), indicating that POG-B4C2N3 is an auxetic material. Additionally, Li decoration on this monolayer was studied to investigate its potential to enhance hydrogen storage through physisorption. The Li@POG-B4C2N3 system shows robust physisorption (adsorption energies ranging from −0.35 to −0.19 eV), high hydrogen storage capacity (8.35 wt %), and effective hydrogen desorption dynamics, positioning this novel material as a promising platform for reversible hydrogen storage.